Effects of clay content and porosity on wave velocities in unconsolidated media wing empirical relations (2004)
"Wave velocities in sandstones are greatly influenced by porosity and clay contents. We formulated new empirical relations for the velocities Vp and Vs in these media which take into account the porosity and clay contents. These relations are Vp=5.57 - 6.47ø - 2.27C1 ø and Vx=3.41 - 4.44ø - 2.23C1 ø, and can be used to compute velocitiesfor various porosities and clay contents. The result compare favourably with those of other works. "